2021
DOI: 10.1038/s41598-021-02902-y
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring interfacial effect in multilayers with Dzyaloshinskii–Moriya interaction by helium ion irradiation

Abstract: We show a method to control magnetic interfacial effects in multilayers with Dzyaloshinskii–Moriya interaction (DMI) using helium (He$$^{+}$$ + ) ion irradiation. We report results from SQUID magnetometry, ferromagnetic resonance as well as Brillouin light scattering results on multilayers with DMI as a function of irradiation fluence to study the effect of irradiation on the magnetic properties of the multilayers. O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…This result is well matched with the above SAED analysis and further proves that the Ga + irradiation forms alloy compositions. The formation of alloys inevitably causes the decrease in PMA, which should be one reason for the increase in the skyrmion density (see Supporting Information Figure S7 for details).…”
Section: Resultsmentioning
confidence: 99%
“…This result is well matched with the above SAED analysis and further proves that the Ga + irradiation forms alloy compositions. The formation of alloys inevitably causes the decrease in PMA, which should be one reason for the increase in the skyrmion density (see Supporting Information Figure S7 for details).…”
Section: Resultsmentioning
confidence: 99%
“…(iii) Finally, we did not directly consider the depth dependence of the ion irradiation. Contrary to lighter He + ions, Ga + ions have a significantly lower penetration depth resulting in a depth dependent damage profile [35,36]. The number of layers of the magnetic multilayer was chosen to ensure that all the layers are affected by the ion irradiation to some extent, as can be seen from the TRIM [56] simulations in Appendix D, while maximizing the number of layers to ensure, e.g., skyrmion stability.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been well established that Ga + and other types of ion irradiation can be used to locally tune the magnetic parameters of single magnetic layers in areas as small as 40 nm [31][32][33][34], but its effect on magnetic multilayers is not yet understood. Very recently, a study investigating the effect of low energy, broad beam He + ion irradiation on [Pt|Co|Ta] ×10 multilayers reported that the magnetic parameters can indeed be controlled, similar to a single magnetic layer [35]. However, compared to He + ions, the penetration depth of Ga + ions is much lower [35,36] and therefore it is not immediately obvious that Ga + ions can also significantly affect the effective magnetic properties of the multilayer stack.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it leads to a modulation of domain wall energy and domain wall width, tuning the PMA is expected to affect the domain wall dynamics both in the creep and in the flow regime. [ 13,14 ] On the other hand, the modification of the DMI strength by ion irradiation [ 13–18 ] was also shown to have an impact on skyrmion stability and dynamics [ 18 ] and is expected to affect the velocity of chiral Néel walls. [ 6,19 ]…”
Section: Introductionmentioning
confidence: 99%